Introduction - María José Azócar; Paula Ballesteros; Marianne González Le Saux (Oñati Socio-Legal Series)
This special issue shows the scholarship developed by a new generation of people dedicated to Socio-Legal Studies in Chile. Our interdisciplinary group has been gathering since the mid-2010s and got formalized in 2018 as the Chilean Law and Society Group. The history of socio-legal studies in Chile shows continuities and ruptures from the beginning of the 20th century to the present. In this special issue, each article offers innovative methodological and theoretical perspectives developed in the last decade in the Socio-Legal field in Chile. At its core, this special issue rethinks law as both a reproducer of structural inequality and as a tool for social transformation.